AN ANALYSIS OF NTPC LTD DEVELOPMENT AND PROSPECTS FOR THE FUTURE! - Mohapatra, Srikanta; Rath, Smruti Ranjan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Power is an inevitable need/demand in the present era of humankind. Every work we perform is directly or indirectly linked with power. Electricity is one of the crucial things in today’s world. It is one of the salient blessings that science has given to us. Electricity has become a part of human life and it is unimaginable to think world without it. Since LPG policy implemented in India, an expeditious growth have been witnessed in Industrialization process due to which in recent time India has emerged as one of the fastest developing country in the world. Power has become the uttermost need to pump the process of growth, leading to overall growth of the nation. NTPC Ltd. is the India’s largest energy conglomerate. NTPC Ltd. has emerged as the no.1 power producing company in India accelerating India’s growth. The present study aims in analytical study of growth of NTPC Ltd. and its future prospects for the overall growth of power sector of India. In this paper the profile of NTPC is studied well and through secondary information sources. A comparison has been fabricated from the past performance of NTPC Ltd. In the present study information were collected solely from the secondary sources. The data analysis for the study was done through comparison of past year wise collected information and data on power operate in India.